Diabetes, dislipidemia y catéter venoso central como factores de riesgo para disfunción de fístula arteriovenosa en pacientes en hemodiálisis - Mariños Malón, Michael Kevyn (2017)
OBJECTIVE: To identify if the diabetes, dyslipidemia and the central venous catheter are risk factors for arteriovenous fistula dysfunction. MATERIAL AND METHODS: Case-control study, which reviewed 168 medical records of patients over 18 years of age with terminal chronic renal disease who were submitted to arteriovenous fistula hemodialysis during the period 2008-2013 at the Hospital Belén de Trujillo. 156 stories, which 78 cases were matched by sex and age with 78 controls. Of these, we identified who presented diabetes, dyslipidemia and previous use of central venous catheter, and subsequently assessed by logistic regression the OR with a 95% confidence interval. RESULTS: The mean age of the cases was 64 ± 13 years and of the controls was 58 ± 17 years. The male sex predominated with 56%. Of the cases, 59% had diabetes, 50% dyslipidemia and 91% had central venous catheter; Of controls, 22% had diabetes, 14% had dyslipidemia, and 38% had central venous catheter. The adjusted OR were for diabetes of 10.31 CI 95% 3.3 - 32.1, dyslipidemia 5.08 CI 95% 1.8 - 13.8 and for central venous catheter 37.03 95% CI 10.2 - 134.8, all with p <0.05. CONCLUSION: Diabetes, dyslipidemia and central venous catheter are risk factors for arteriovenous fistula dysfunction